2022
DOI: 10.1155/2022/9528046
|View full text |Cite|
|
Sign up to set email alerts
|

Home Care System for Mobility Disabilities Based on Intelligent Perception

Abstract: In order to explore how to realize home care for the elderly with mobility difficulties, this paper proposes a home care system for the elderly with mobility difficulties based on intelligent perception. This method explores the research of home care for mobility disabilities by recommending key technical problems and solutions based on information represented by intelligent perception. The research shows that the home care system based on intelligent perception can effectively solve the nursing problems of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the realm of elderly healthcare, Switzerland introduced the concept of 'local aging' in the 1960s, marking a signi cant shift in how elderly care is approached. This shift has seen a move away from institutional care in favor of community-based and home-based services [5]. In contrast, Macau faces distinct challenges in providing long-term care due to being the second world's most densely populated region, with 20,620 individuals per square kilometer [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the realm of elderly healthcare, Switzerland introduced the concept of 'local aging' in the 1960s, marking a signi cant shift in how elderly care is approached. This shift has seen a move away from institutional care in favor of community-based and home-based services [5]. In contrast, Macau faces distinct challenges in providing long-term care due to being the second world's most densely populated region, with 20,620 individuals per square kilometer [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the face of limited health care resources and rapidly increasing health care costs, implementing a personalized and integrated healthcare system has become an urgent topic for studying and addressing in elderly societies [4].In the realm of elderly healthcare, Switzerland introduced the concept of 'local aging' in the 1960s, marking a signi cant shift in how elderly care is approached. This shift has seen a move away from institutional care in favor of community-based and home-based services [5]. In contrast, Macau faces distinct challenges in providing long-term care due to being the second world's most densely populated region, with 20,620 individuals per square kilometer [1].…”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%